2023
DOI: 10.1590/fst.117122
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies for the antiparasitic activities of Azadirachta indica extract

Abstract: Coccidiosis and helminthiasis are two parasitic diseases that harm both health and the economy. The present study aimed to assess the effect of Azadirachta indica leaf extracts (AILE) as an anti-parasitic modulator during murine coccidiosis as well as helminthic infection. Phytochemical analysis using FT-IR showed the presence of eleven compounds. A dose-dependent efficacy was observed in all experiments. At the highest concentration (200 mg/mL), time consumed to induce paralysis and death for worms was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…The cuticular surface of the worms treated with MyE showed extraordinary modifications, including significant shrinking. This agreed with Abu Hawsah et al . (2023) who described how anthelmintic treatments caused modifications to the worm’s body surfaces.…”
Section: Discussionsupporting
confidence: 92%
“…The cuticular surface of the worms treated with MyE showed extraordinary modifications, including significant shrinking. This agreed with Abu Hawsah et al . (2023) who described how anthelmintic treatments caused modifications to the worm’s body surfaces.…”
Section: Discussionsupporting
confidence: 92%
“…It has been established that one of the numerous target locations via which anthelmintic agents interact with parasites is their cuticle. This was in agreement with Abu Hawsah et al (2023) description of how anthelmintic treatments altered the surfaces of the worms' bodies and might cause paralysis and worm death.…”
Section: Discussionsupporting
confidence: 92%
“…Here, the anthelmintic activity of P. granatum was modeled after that of earthworms. Due to the physiological similarities between E. fetida worms and several intestinal round worms that infect humans, earth worms have been employed as the model in many studies for the evaluation of anthelmintic activities (Abu Hawsah et al, 2023). The 200 mg/mL concentration of P. granatum produced a significant anthelmintic activity in the current in vitro study that is comparable to the anthelmintic drug, mebendazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In another attempt, Hawsah et al synthesized selenium nanoparticles (Se NPs) from Azadirachta indica leaves extract using the green synthesis approach; then, they utilized Se NPs for applications of anthelminthic and cytotoxic activities. 15 Kasem et al in another study evaluated the in vitro anticoccidial activities of an ultrasonicated ethanolic extract of Rosmarinus of f icinalis (UEERO) and its chitosan-based nanoparticles (UEERO-Cs NPs) on Eimeria tenella oocysts of chickens. 16 Also, Lin et al in their findings indicated that the anticoccidial efficacy of Halofuginone hydrobromide (HF) was significantly enhanced after being encapsulated in polymer micelles and further demonstrated the potential protective application of nanoencapsulating anticoccidial drugs as a promising approach to control coccidiosis in poultry.…”
Section: Introductionmentioning
confidence: 99%